2015
DOI: 10.1002/2014jc010464
|View full text |Cite
|
Sign up to set email alerts
|

Field observations of wave‐driven circulation over spur and groove formations on a coral reef

Abstract: Spur and groove (SAG) formations are found on the forereefs of many coral reefs worldwide.Modeling results have shown that SAG formations together with shoaling waves induce a nearshore Lagrangian circulation pattern of counter-rotating circulation cells, but these have never been observed in the field. We present results from two separate field studies of SAG formations on Palmyra Atoll which show their effect on waves to be small, but reveal a persistent order 1 cm/s depth-averaged Lagrangian offshore flow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
8
28
1
Order By: Relevance
“…There is an additional, albeit small, influence of the cross‐shore advective acceleration term. On the other hand, the alongshore tidal budget at 12mS suggests that advective acceleration is an equally important contributor to the momentum budget as the bottom drag, similar to what Rogers et al () found over a spur and groove formation on the fore‐reef. We hypothesize that the imbalance at the 12mS mooring is associated with a local acceleration of the flow.…”
Section: Discussionsupporting
confidence: 81%
“…There is an additional, albeit small, influence of the cross‐shore advective acceleration term. On the other hand, the alongshore tidal budget at 12mS suggests that advective acceleration is an equally important contributor to the momentum budget as the bottom drag, similar to what Rogers et al () found over a spur and groove formation on the fore‐reef. We hypothesize that the imbalance at the 12mS mooring is associated with a local acceleration of the flow.…”
Section: Discussionsupporting
confidence: 81%
“…Physical measurements in a SaG system at Palmyra Atoll, a reef exposed to oceanic swell from the North Pacific, supported the modelling results, showing a persistent 1 cm s −1 offshore flow over the spurs and onshore flow over the grooves at depths of 8-11 m (Rogers et al, 2015). However, Rogers et al (2015) acknowledge that the model results for shallow zone have yet to be verified with field data as instruments were insufficiently shallow, further highlighting the difficulties of collecting data in the shallow, highly dynamic zone. In Grand Cayman Island, a reef exposed to the gentler waves of Caribbean, Roberts et al (1977) reported that currents in grooves seemed to be tidally dominated.…”
Section: Accepted M Manuscriptsupporting
confidence: 52%
“…(Palmyra Atoll; Rogers et al, 2015) and 4° (Molokai, Hawaii; Rogers et al, 2013). This highlights that gradient and width of the reef slope are determining factors in SaG formation.…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
See 2 more Smart Citations